2009
DOI: 10.1111/j.1600-0501.2009.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of zirconia and titanium dental implants: a histological and histomorphometrical study in the maxilla of pigs

Abstract: No statistical difference between implants could be demonstrated with any of the methods used. The limited number of animals per group, however, does not allow to conclude that there is no difference in osseointegration between the two types of implants, although the data tend to suggest such a trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
108
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 17 publications
9
108
0
5
Order By: Relevance
“…Therefore, there are far fewer reports on treatment to roughen zirconia ceramic surfaces compared with reports for titanium surfaces. There have been studies regarding surface modifications, involving machining 15) , sandblasting [16][17][18] , and calcium phosphate coating on ceramics 14,19) . In recent years, several studies have been reported in which zirconia ceramic surfaces were etched or sandblasted much like on titanium implant surfaces [21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there are far fewer reports on treatment to roughen zirconia ceramic surfaces compared with reports for titanium surfaces. There have been studies regarding surface modifications, involving machining 15) , sandblasting [16][17][18] , and calcium phosphate coating on ceramics 14,19) . In recent years, several studies have been reported in which zirconia ceramic surfaces were etched or sandblasted much like on titanium implant surfaces [21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…However, surface modification of zirconia ceramics is technically difficult 11) . Thus, only a very small number of studies have been performed on their surface topography and the response of the surrounding tissue 8,10,[12][13][14][15][16][17][18][19] In the clinical application of zirconia ceramic implant bodies, it is essential to examine the effects of their surface topography on the surrounding tissue. The aims of this study were to produce rough surfaces on zirconia by laser treatment and to examine how changes in surface topography affect tissues surrounding zirconia implants.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The reliability of RFA to predict implant stability and to determine loading time remains questionable. 14 Use of histological and histomorphometric methods 15,16 for the purpose requires sacrifice of the area of interest along with the implant. A radiologic study provides only two dimensional morphological quantification of the area of interest in one single plane.…”
Section: Discussionmentioning
confidence: 99%
“…In three phase bone scan with SPECT study, bone seeking pharmaceutical agent methylene di-phophonic acid (MDP) added to gamma photon emitting radionuclide Technetium 99 (15)(16)(17)(18)(19)(20) is injected by intravenous route resulting in distribution of radioactivity in all three planes and phases (vascular, blood pool and bone phase) including the area of interest which can be detected using gamma camera. The technique utilizes radionuclide tracer targeted imaging based on detection of gamma rays emitted by the radionuclide when embedded in biological specific compounds after intravenous administration.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have been conducted to determine the nature of the interaction that occurs between the metal and the tissue [2][3][4][5] called osseointegration, in which the bone-implant unit becomes an anatomical structure 6 and supports patient function without causing injury.…”
Section: Introductionmentioning
confidence: 99%